Long-lived radionuclides (129I and 236U) as water mass tracers in the North Atlantic and Fram Strait - Wefing, Anne-Marie; id_orcid:0 000-0001-6855-6062; Castrillejo, Maxi; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Vockenhuber, Christof; Rutgers van der Loeff, Michiel; Lherminier, Pascale (Copernicus, 2019)
ISSN:1029-7006 ISSN:1607-7962